Le désir d’une autre vie - Barbara Carnevali (Itinéraires)
This article offers a counter-reading of Proust, on the basis of a critique of René Girard’s famous hermeneutics in Mensonge romantique et vérité romanesque. Observing the bases and implications of “mimetic” anthropology and of Girard’s dark vision of desire, conceived as an alienation or degradation of the self (thus mistaken for “envy”), it aims to shift the perspective and adopt a sympathetic view to explore the desire for another life manifested by characters in the Recherche. It also aims to rehabilitate through sustained philosophical analysis three often devalued components of human experience: love, hope, and snobbery.